Inoculation of bacterial consortium increases rice yield (Oryza sativa L.) reducing applications of nitrogen fertilizer in San Martin region, Peru - Ríos-Ruiz W.F. (2020)
Rice feeds more than 50% of the population worldwide, representing a great energy contribution in low-income families. The exaggerated use of synthetic chemical fertilizers to maintain high levels of yield causes alterations in the physical, chemical and biological quality of the soils. A sustainable alternative is the use of beneficial microorganisms that promote plant growth in crops. The objective of the study was to isolate and evaluate the Plant Growth Promoting (PGP) traits of rhizospheric rice bacteria in soils of the San Martin region, evaluate the effect of promoting growth in rice under pot experiments conditions and finally evaluate the effect of selected strains on the yield under different doses of nitrogen fertilizer under field conditions. Initially, 27 strains were selected for their diazotrophic characteristics and characterized by PGP traits. Through a multivariate analysis of main components, five strains were selected and evaluated in pot experiments. In this stage, the rice seeds were inoculated with the five selected strains at the rate of 109 CFU g?1 and were evaluated at 135 days. The strains showed that the parameters such as Shoot Dry Weight (SDW), tillering and grain quality were superior and even similar between inoculated treatments receiving doses of 50% Nitrogen (N) (75 kg N ha?1) and treatment receiving full dose (150 kg of N ha?1). For the field experiments, Burkholderia ubonensis la3c3, Burkholderia vietnamiensis la1a4 and Citrobacter bitternis p9a3m were selected, which were inoculated in a consortium at a rate of 109 CFU mL?1 in the nursery stage and at the time of transplantation. Grain yield was higher but not significant between 2.5 and 13.5% in inoculated treatments receiving 75% and 100% (150 kg N ha?1) of the nitrogen fertilizer dose compared to the treatment without inoculation and without fertilization. Grain quality was superior in inoculated treatments versus non-inoculated treatments, reaching specific increases of 32.8% (N), 45.5% (P) and 27.9% (K) in inoculated treatments receiving low doses of N fertilizer (25%) versus treatment receive a full dose of fertilizer, also a significant increase of 2.5% in the percentage of whole grain, with respect to mill quality. The rentability (14.7–88.6%) and the utility (17.7–94.1%) were also higher in inoculated treatments. It is concluded that the use of selected native bacterial consortiums reduces the use of nitrogen fertilizer by up to 25%, increasing the productivity of rice cultivation in the San Martín region. © 2020